1998
DOI: 10.6028/jres.103.037
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the effects of longitudinal resistance in multi-series-connected quantum Hall effect devices

Abstract: Many ac quantized Hall resistance experiments have measured significant values of ac longitudinal resistances under temperature and magnetic field conditions in which the dc longitudinal resistance values were negligible. We investigate the effect of non-vanishing ac longitudinal resistances on measurements of the quantized Hall resistances by analyzing equivalent circuits of quantized Hall effect resistors. These circuits are based on ones reported previously for dc quantized Hall resistors, but use additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The relative change in the quantized Hall resistance using a tripleseries connection in dc can be calculated from a mathematical model of the QHR [4]. In that reference an offset of less than 0.001 µΩ/Ω was found with typical leads and longitudinal resistance.…”
Section: Type B Evaluation Of Standard Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…The relative change in the quantized Hall resistance using a tripleseries connection in dc can be calculated from a mathematical model of the QHR [4]. In that reference an offset of less than 0.001 µΩ/Ω was found with typical leads and longitudinal resistance.…”
Section: Type B Evaluation Of Standard Uncertaintymentioning
confidence: 99%
“…This improves the sensitivity [2] but the winding resistance must be measured to correct the value of each resistor. Since this bridge measures two-terminal resistors, we use the tripleseries connection technique to reduce errors in measurements of the QHR, as described in [4]. In a condition of balance, the bridge equations are: (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Under these current and magnetic field conditions, the drain contact pad D ′ and the potential probe contact pads 1 ′ , 3 ′ , and 5 ′ at the device periphery are at higher potentials than contact pads S ′ , 2 ′ , 4 ′ , and 6 ′ . These current and flux density directions are chosen to be consistent with those we have used in earlier calculations [ 19 , 22 23 ].…”
Section: Equivalent Electrical Circuit Of An Ac Qhe Standardmentioning
confidence: 99%
“…Diamond-shaped voltage generator arrays of Ricketts and Kemeny [ 18 ] are employed in the equivalent circuit of the QHE device, rather than the ring-shaped voltage generator arrays introduced later by Delahaye [ 24 ] and then subsequently used by Jeffery, Elmquist, and Cage [ 25 ]. Although both arrays give essentially identical results [ 22 ], the calculations are much simpler with the diamond arrays when longitudinal resistances are included in the circuits [ 22 ]. We therefore use diamond arrays.…”
Section: Equivalent Electrical Circuit Of An Ac Qhe Standardmentioning
confidence: 99%
“…Very detailed analytical studies of QHE circuits have been reported in the literature [4], nevertheless, if the measurement circuit is not oversimplified, the equations become very complex [5]. Numerical techniques are useful [6] in the study of such a problem, allowing quick tests of solutions corresponding to different values of the circuit parameters.…”
Section: Introductionmentioning
confidence: 99%